Analisis Strategi Kepala Sekolah dalam Meningkatkan Kompetensi Guru: (Study Kasus di SD Insan Terpadu Sumberanyar dan MI Raudlatul Munadhirin Pandean) - Firdaus Ainul , Firdaus Ainul (LP3M Universitas Islam Zainul Hasan Genggong, 2017)
The background of the writing of this title is the low competency of teachers in Indonesia, then to improve the competence, need the appropriate strategies to be carried out by the principal in order to improve the competency. The aim of this study was to determine the general picture of teacher competence, competence improvement strategy that has been done by the principal as well as the right formulation to increase the competence of teachers. In this study used descriptive qualitative method, which did not use numbers, but used a description of the data that corresponded to the reality in the field. This research was conducted in two schools, namely SD Insan Integrated Sumberanyar and MI. Raudlatul Munadhirin Pandean. And the results of this study indicated that 1). Teachers in SD Insan Integrated Sumberanyar were largely S-1 and certified 13 people, but there were some policies that principals were less precise about the academic qualifications of teaching subjects. While in MI. RaudlatulMunadhirin Pandean, most of the teachers had S-1, only 3 people who have not qualified academic S-1 because it was still in the stage of completion. And 9 people were already certified. 2). Almost the same of strategies undertaken by the school principal of SD Insan Integrated and MI. Raudlatul Munadhirin in enhancing the competence of teachers, as to include teachers in workshops and seminars, training by bringing in speakers from outside, but there were several different like in MI. Raudlatul Munadhirin, there is an IT training, while in SD Insan Integrated nothing. Furthermore, in SD Insan Integrated conducted a comparative study into the advanced school, whereas in Mi. Raudlatul Munadhirin has never been done. Formulations offered by researcher associated with increased competency of teachers, they were: a). Proactive to include teachers in the workshop which directed, planned, and sustainable. b). Further study of the S-2. c). Utilization of the journal, both the article and research. d). Doingthe equivalency of academic qualification and certification. e). Making effectiveness the teachers in KKG and MGMP f). Holdingcourseor IT training and foreign language (English) g). Coaching attitude and personality. h). providing motivation through reward and punishment.